An Overview of Autonomy in Higher Education: A Systematic Review of the Meaning, Dimensions, Challenges, and Future Directions of Autonomy - Teshome, Samson Worku (Lembaga Yasin AlSys, 2025)
Autonomy in higher education has become a central focus in academic discourse as institutions confront the evolving demands of globalization, accountability, and governance reform. This systematic literature review synthesizes current research on the concept of autonomy in higher education, examining its definitions, core dimensions, prevailing challenges, and future trajectories. Employing the PRISMA framework, a comprehensive search and selection process resulted in the inclusion of 44 scholarly articles. The analysis identifies four principal dimensions of institutional autonomy: academic, financial, organizational, and staffing. Key challenges include the tension between autonomy and accountability, increasing external pressures from governments and market forces, and the implications of internationalization. The review also outlines emerging directions for research and practice, including the development of adaptive governance frameworks and the strategic use of digital technologies to strengthen institutional independence. The findings emphasize the role of autonomy in promoting innovation, academic excellence, and institutional resilience amidst growing global and regulatory pressures. This review offers valuable insights for policymakers, university leaders, and scholars, contributing to the broader dialogue on higher education governance.